A Literature Review on Managing Problematic Student Behavior in Elementary Schools through Guidance Services - Amar Salahudin; Izmi Watri Saleh (Institution of Scientific Publishing and Publication of the Yayasan Dzaky Elmumtaz Qurani, 2025)
Problematic behavior among elementary school students is a common issue in educational settings and can hinder students’ academic and social development. The management of problematic behavior requires approaches that are aligned with children’s developmental characteristics, one of which is the provision of guidance services in schools. This study aims to analyze the existing literature on the management of problematic behaviors among elementary school students through guidance services. The research employed a qualitative literature review method by identifying and analyzing various relevant scholarly sources, including books and national as well as international journal articles. The data were analyzed using content analysis with a thematic approach. The findings indicate that problematic behaviors in elementary school students are closely related to children’s social and emotional development. Guidance services play a crucial role in managing problematic behaviors through preventive and developmental approaches, as well as the implementation of guidance techniques such as group guidance, basic individual counseling, and psychoeducational activities. Furthermore, collaboration among teachers, counselors, and parents emerges as a key supporting factor for the successful management of student behavior. This study concludes that strengthening guidance services in a systematic and sustainable manner is essential for creating a conducive learning environment and supporting the development of positive behaviors among elementary school students.